Labor and informal work in North-South relations: a study on Iberian countries and Latin-America - Estanque, Elísio (2021)
Departing from the North/South dialogue, and considering the historical relations between the Iberian countries and Latin America (la), the aim is to analyze trends, contrasts and asymmetries in different scales. Asymmetric powers and dynamic tensions and negotiations are discussed both in the world-system scale and in the European Union context. In the light of recent transformations in international capitalism, our paper addresses, on the one hand, the phenomenon of informality / labor precariousness and, on the other, resorting to a more prospective record, diagnoses some of the recent challenges of technological innovation and digitalization. Considering an ongoing project related to these issues (Latwork), our analysis encompasses the sociological knowledge developed by diverse research teams on the labor field, namely regarding informality and technological innovation. For this purpose, we also gather quantitative data on research teams from the universities of la countries (Brazil, Argentine and Chile) using factorial analysis. The aim is to foster decent work, particularly in the Latin American countries under study, where, as we know, the scourge of informality and vulnerability of the working classes is a structural feature that remains from colonial heritage till the early peripheral industrialization. Thus, the spirit of our study lies in the effort to understand the changes taking place in the field of labor relations at a time when global capitalism is at a crossroads in the face of the brutal impacts of the Covid-19 pandemic.